Caracterização taxonômica e funcional da comunidade microbiana envolvida no processo de atenuação natural de solos contaminados com querosene : Taxonomic and functional characterization of the microbial community involved in the process of natural attenuation of jet fuel-contaminated soil - Hidalgo Martinez, Kelly Johanna, 1985- (2019)
Orientador: Valéria Maia Merzel